KUALITAS PELAYANAN PEGAWAI DALAM PENERBITAN SURAT KETERANGAN PENDAFTARAN TANAH (SKPT) PADA BADAN PERTANAHAN NASIONAL KABUPATAN ENREKANG - Makmur, Rahmawati; Mappamiring, Mappamiring; Rahim, Samsir (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2022)
ABSTRACTThe purpose of this study was to find out and describe the quality of service in the issuance of SKPT at the National Land Agency Office of Enrekang Regency. This study used qualitative research. The number of informants in this study were 10 people. The data collection used observation, documentation, and direct interviews. The results showed that the service quality of employees in the issuance of Land Certificates (SKPT) at the National Land Agency of Enrekang Regency was good, based on 5 indicators, namely Tangibles at the Enrekang Regency BPN Office on the provision of adequate facilities and infrastructure. Reliability with the service process was 50 minutes, the officer was able to provide the explanation needed by the SKPT. Responsivines at the Enrekang Regency BPN Office had responded to SKPT complaints when problems occur in the service process. The officer had provided assurance of the ease of procedure to the public in the service. Empathy, it seen that the officers had been friendly and polite in providing services to the community.Keywords: Quality, Service, SKPT Issuance